Gold- and Silver-Catalyzed Glycosylation with Pyranone Glycosyl Donors: An Efficient and Diastereoselective Synthesis of α-Anomers - Liu, Wenfeng; Chen, Qian; Liang, Jiashen; Du, Zhiyun; Zhang, Kun; Zheng, Xi; O’Doherty, George A. (Synlett, 2015)
A mild, efficient and diastereoselective gold- and silver-catalyzed O-glycosylation with pyranone glycosyl donors is described. The reactions led to the formation of α-anomers in up to 91% yield with good diastereoselectivities.
Keywords: alcohols; carbohydrates; catalysis; diastereoselectivity; glycosylation